Immediate effects of electrical stimulation on serratus anterior muscle activity in people with hemiplegia post-stroke - Palak Anand Kakwani; Ramesh Debur (European Journal of Translational Myology)
Upper limb impairment occurs in approximately 80% of stroke survivors, with altered scapular kinematics playing a key role in dysfunction. Serratus anterior weakness post-stroke contributes to abnormal scapular motion, limiting shoulder and arm function. This study explored whether Electrical Stimulation (ES) could immediately enhance serratus anterior activity in individuals with post-stroke hemiplegia. A pre-post intervention design was used involving 19 individuals within three months post-stroke. Surface Electromyography (sEMG) recorded serratus anterior activity during a forward reach task. The Fugl-Meyer Assessment (FMA) was also administered. Participants received 20 minutes of ES targeting the serratus anterior, after which sEMG and FMA were reassessed. Wilcoxon signed rank test compared pre- and post-intervention sEMG values. Statistical analysis showed a significant change in the area under the curve value(p < 0.01) but no significant change in RMS value. There was no change in FMA scale. Electrical stimulation showed significant changes in the muscle activity of the serratus anterior, indicating a reduction in the cost of the muscle work done during the forward reach task.